PENCEGAHAN SEKS BEBAS MELALUI PENGUATAN NILAI RELIGIUS DI SMAN 1 JIWAN - Angger Gede Nararia; Mochamad Ervan Nurkhodhi; Najwa Dwi Nurlita; Revita Putri Zhaharani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The phenomenon of premarital sex among teenagers is increasingly prevalent in the modern era, driven by unfiltered access to information. One of the main contributing factors is the decline in religious values among youth. This community service aims to educate students of SMAN 1 JIWAN about preventing free sex behavior through the strengthening of religious values. The methods used include interactive lectures, educational video screenings, group discussions, and digital quiz-based assessments. The result shows improved student understanding of the dangers of free sex and the importance of moral self-control. This initiative is expected to serve as a preventive step in shaping responsible and religious teenagers.